Counterterrorism Legislation and Its Impacts on Human Rights in Malaysia - bin Idris, Noor Maarof; Khoo, Ying Hooi (UI Scholars Hub, 2025)
In the aftermath of 11 September 2001, terrorism overshadowed other global security concerns. Since then, there has been significant growth in security and counterterrorism legislation and policies worldwide. The United Nations Security Council (UNSC) Resolution 1373 (2001) and 1456 (2003) authorized states to implement national legislative measures to combat terrorism while emphasizing the promotion and protection of human rights and the rule of law. In Malaysia, counterterrorism efforts have been reinforced through the Security Offences (Special Measures) Act 2012 (SOSMA), the Prevention of Crime Act 1959 (POCA) (as amended in 2015), and the Prevention of Terrorism Act 2015 (POTA). This study critically examines these key pieces of Malaysian legislation related to counterterrorism and assesses their impact on human rights. The study explores the government’s securitization approach to managing perceived terrorism threats through this legislation. It specifically investigates how preventive detention provisions in these laws affect human rights in Malaysia, particularly the right to life and personal liberty as enshrined in Article 5 of the Federal Constitution. The findings revealed instances of